Growth rhythm of Vochysia divergens Pohl (Vochysiaceae) in the Northern Pantanal - Machado, Nadja Gomes; Sanches, Luciana; Aquino, Aryadne Márcia; Silva, Ludymilla Barboza da; Novais, Jonathan Willian Zangeski; Biudes, Marcelo Sacardi (Acta Scientiarum. Biological Sciences, 2015)
The Pantanal is the largest wetland in the world, characterized by high biodiversity, but large areas have been invaded by Vochysia divergens, a flood-adapted pioneer and native tree of the riparian forest and Brazilian Savanna. Seasonality in rainfall causes annual rhythms in the tree’s physiology, in which climatic stress factors induce a cambial dormancy in trees and, in consequence, growth zones in the trunk. Current analysis evaluates the seasonal variation of the diameter increase of V. divergens specimens in a seasonal floodable forest of the Northern Brazilian Pantanal. Field sampling was conducted between January and December 2012. Air temperature, relative humidity and precipitation were measured at a micrometeorological station, water level was measured by graded tape, and soil water content was measured by a portable TDR sensor. Diameter growth was monitored by dendrometric bands and aboveground litter production was sampled by litter traps. The annual diameter increase was 4.0 mm. There was correlation between diameter increment and climate and phenology, with the highest increase during the flooding period and the lowest during the dry season and reproductive period. Climate and phenology affected the growth rhythm of V. divergens.